428 Ulna Shortening Osteotomy Using a Dorsal DCP Plate Versus Volar Low-Profile Plate: Which Is Superior?. (19th August 2022) - Manley, L; Rabbani, M; Gupta, N; Macmillan, A; McKee, A; Norris, R; Jones, J
Abstract: Aim: There is limited literature comparing differing techniques and equipment used in ulna shortening osteotomy. This study reviewed operative outcomes of ulna osteotomies across one NHS Trust. Our aims were to compare outcomes of two different operative techniques: dorsal-approach DCP plates versus volar-approach low profile plates and to evaluate the impact of plate size on union rates. Method: We performed a retrospective review of all patients undergoing an ulna shortening osteotomy between 2016–2021 at North West Anglia Foundation Trust. We reviewed patient demographics, surgical technique, plate size, complications, union rates and need for reoperation. Outcomes between two operative techniques were compared using Fisher's exact test. Results: 32 patients were identified. 21 had a dorsally placed DCP plate using the Stanley jig, 11 had a volar low-profile plate using alternative systems. The majority of DCP plates were 6 or 7 holes. One 5-hole plate was used, resulting in the only case of non-union. Overall complication rate was 41%. 38% of patients with a dorsal plate had symptoms of plate irritation post-operatively. 5 needed removals, which was significantly greater than in the volar plate group (rate of 0%, p = 0.03). There were no cases of nerve damage and one case of CRPS in the volar low-profile plate group. Conclusions: We found that a 5-hole DCP plate should be avoided and dorsally placed DCP plates led to more cases of plate irritation requiring removal. Overall, rates of union and improvements in function and pain scores were acceptable and comparable regardless of surgical technique used.